2021
DOI: 10.1038/s41598-021-86593-5
|View full text |Cite
|
Sign up to set email alerts
|

Exercise rapidly alters proteomes in mice following spinal cord demyelination

Abstract: Exercise affords broad benefits for people with multiple sclerosis (PwMS) including less fatigue, depression, and improved cognition. In animal models of multiple sclerosis (MS), exercise has been shown to improve remyelination, decrease blood–brain barrier permeability and reduce leukocyte infiltration. Despite these benefits many PwMS refrain from engaging in physical activity. This barrier to participation in exercise may be overcome by uncovering and describing the mechanisms by which exercise promotes ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…revealed that the alternation of genes is related to the metabolism pathway. They indicated that the expression protein of Pgam2 in glycolysis and Ndufb9, Ndufv3, and mt-Nd3 associated with mitochondria significantly changed by exercise training [ 2 ]. In this regard, we found that physical activity improved the motor function, proinflammatory cytokine, and demyelination of the Multiple sclerosis rats.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…revealed that the alternation of genes is related to the metabolism pathway. They indicated that the expression protein of Pgam2 in glycolysis and Ndufb9, Ndufv3, and mt-Nd3 associated with mitochondria significantly changed by exercise training [ 2 ]. In this regard, we found that physical activity improved the motor function, proinflammatory cytokine, and demyelination of the Multiple sclerosis rats.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has indicated that physical activity could modulate the brain’s structure and connectome [ 38 , 39 ]. Moreover, based on the literature review, exercise training might ameliorate fatigue, depression, neurogenesis, neuroprotection, remyelination, and cognition [ 2 , 40 , 41 ]. Lourenco and colleagues demonstrated that aerobic exercise could increase the expression level of the Nrf2 as a vital transcription factor and antioxidant enzymes activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations